Magnetic resonance imaging pelvimetric measurements as predictors for emergent cesarean delivery in obstructed labor - Ryuichi Shimaoka; Yuichiro Takahashi; Hitomi Ono; Masako Matsui; Kazuhiko Asai; Shigenori Iwagaki (Elsevier, 2023)
Objective: This study aimed to investigate the usefulness of various magnetic resonance imaging (MRI) pelvimetric parameters for predicting emergent cesarean delivery due to obstructed labor. Study design: This was a prospective observational study. MRI pelvimetry was performed in cases of a clinically suspected maternal narrow pelvis, maternal short stature, fetal overgrowth, and abnormal placental position. MRI pelvimetry was performed at 34.7 ± 4.2 gestational weeks using a 1.5 T MRI system. The pelvic inlet angle, pelvic inclination, obstetric conjugate, sacral outlet diameter (SOD), and coccygeal pelvic outlet were measured in the sagittal section. The interspinous diameter and intertuberous diameter were measured in coronal sections. Fetal anomalies, cesarean deliveries before the onset of labor, and non-reassuring fetal status were excluded from the analysis. Results: MRI pelvimetry was performed in 154 patients. After excluding 76 cases, including 19 cases of absolute cephalopelvic disproportion, 78 cases of trial of labor were included. Of these, 63 were vaginal deliveries and 15 were emergent cesarean deliveries due to obstructed labor. The cut-off value for body mass index (BMI) was 22.2, with an area under the curve (AUC) of 0.69, for predicting obstructed labor. The cut-off value for the SOD was 10.7 cm with an AUC of 0.69. BMI alone had a sensitivity of 80%, specificity of 66%, positive predictive value (PPV) of 36%, and negative predictive value (NPV) of 93%. When BMI and SOD were combined, sensitivity was 53%, specificity was 90%, PPV was 57%, and NPV was 89%. The odds ratio for emergent cesarean delivery was 5.42 (95% confidence interval 1.06-27.6, p = 0.041) if the SOD was less than the cut-off value in the binomial logistic regression analysis in cases with an BMI > 22. Conclusion: We confirmed that MRI pelvimetry was a reliable tool for better patient selection for obstructed labor. The SOD was the best predictor of obstructed labor, with a cut-off value of 10.7 cm for women with a low BMI.